2015
DOI: 10.4274/jcrpe.1919
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of 46,XY Pure Gonadal Dysgenesis: Spontaneous Breast Development and Menstruation

Abstract: 46,XY pure gonadal dysgenesis (Swyer syndrome) is characterized by normal female genitalia at birth. It usually first becomes apparent in adolescence with delayed puberty and amenorrhea. Rarely, patients can present with spontaneous breast development and/or menstruation. A fifteen-year-old girl presented to our clinic with the complaint of primary amenorrhea. On physical examination, her external genitals were completely female. Breast development and pubic hair were compatible with Tanner stage V. Hormonal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…Gonadal tumors were found in the probands (gonadoblastoma in P1 and dysgerminoma/gonadoblastomain P2). In accordance with other reports 7072 , the presence of positive steroidogenic markers (such as CYP11A1 and CYP19) may rationalize the observed breast development and pubertal uterus size. Tumor steroid production might also have increased skeletal bone maturation, accounting for the heights of the sisters (shorter than expected in patients with 46, XY CGD 68 ).The presence of pluripotential aberrant germ cells was revealed by high nuclear OCT3/4 immuno-expression.…”
Section: Discussionsupporting
confidence: 92%
“…Gonadal tumors were found in the probands (gonadoblastoma in P1 and dysgerminoma/gonadoblastomain P2). In accordance with other reports 7072 , the presence of positive steroidogenic markers (such as CYP11A1 and CYP19) may rationalize the observed breast development and pubertal uterus size. Tumor steroid production might also have increased skeletal bone maturation, accounting for the heights of the sisters (shorter than expected in patients with 46, XY CGD 68 ).The presence of pluripotential aberrant germ cells was revealed by high nuclear OCT3/4 immuno-expression.…”
Section: Discussionsupporting
confidence: 92%
“…Despite complete GD, the normal breast development observed in the current series needs to be pointed out, and it could explain the delay before diagnosis. This is not typically reported in Swyer syndrome (unlike in complete androgen insensitivity syndrome, where aromatization of androgen leads to breast growth), although it has been reported occasionally . Breast growth could be related to hormone activity of the tumor.…”
Section: Discussionmentioning
confidence: 93%
“…However, the breast development was not adequate in all the reports and did not achieve Tanner stage V, as in our patient. Catli et al reported a case of a 46,XY CGD teenager with adequate breast development and irregular menstrual periods [6]. There has also been a case of Swyer syndrome reported with adequate development of secondary sexual features and secondary amenorrhoea [10].…”
Section: Discussionmentioning
confidence: 99%